Improving Student Learning Outcomes by using Blog Media in Geography Subjects - Siti Hajar; Lutfi Lutfi; David Adjei; Emmanuel Danladi Ndan (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research aims to improve student learning outcomes by using blog media. The background of this research is that learning is still teacher-centered, more teachers only use the lecture method, and do not use learning media. Students are less enthusiastic when studying geography, they often fall asleep in class. This causes low student learning outcomes, so the method used to overcome this problem is to use blog media. Methodology: The method used in this research is Classroom Action Research with a sample of 34 class XI high school students. The instruments used were lesson plans, observation sheets, interview sheets and geography learning results tests. This research was conducted at Senior High School Nusantara. Main Findings: Theresearch results showed that student learning activities experienced significant changes and the average N-Gainin cycle I was 0.33 and increased to 0.52 in cycle II. Based on these results, it can be proven that the use of blog media is effective in improving geography learning outcomes Novelty/Originality of this study:In an effort to enrich the learning process, this research allows the use of blog media as an innovative tool. By integrating information and communication technology through blogs, it is hoped that it can create a more dynamic and interactive learning environment. The focus of this research is not only on technological aspects, but also on the impact of using blog media on students understanding and involvement in understanding geographical concepts.